Identification and functional characterization of prognosis-related ferroptosis-associated lncRNAs in colorectal cancer - Ge, Xiaoxu; Xu, Jiasheng; He, Jinjie; Wang, Jian; Qian, Yucheng (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) is a significant global health burden, with current treatment strategies often limited by the TNM classification system’s inability to fully capture tumor heterogeneity. This study aims to explore the biological functions and prognostic value of differentially expressed ferroptosis-related long non-coding RNAs (DEFRlncRNAs) in CRC.MethodsWe utilized the TCGA database to identify DEFRlncRNAs associated with CRC prognosis. Through multivariate Cox regression analysis, we constructed a prognostic model and selected three key lncRNAs: Lnc-SH2D3A-2, Lnc-LSS-1, and Lnc-PEX11G-4. We assessed their expression in CRC and normal colonic epithelial cell lines using qPCR. Further functional assays included ferroptosis induction with RSL3 and Erastin, cell viability assessments, immunofluorescence staining for lipid peroxidation, and Western blot analysis of ferroptosis-related proteins.ResultsOur analysis identified 15 DEFRlncRNAs significantly associated with CRC prognosis, with Lnc-SH2D3A-2, Lnc-LSS-1, and Lnc-PEX11G-4 showing high basal expression in CRC cell lines. Knockdown of Lnc-LSS-1 and Lnc-PEX11G-4 in HT29 and DLD1 cells resulted in significant inhibition of ferroptosis induced by RSL3 and Erastin. The mechanism behind the suppression of ferroptosis by knockdown of Lnc-LSS-1 and Lnc-PEX11G-4 may involve the inhibition of lipid peroxidation and the upregulation of GPX4 expression.ConclusionDEFRlncRNAs, particularly Lnc-LSS-1 and Lnc-PEX11G-4, play crucial roles in regulating ferroptosis in CRC. These lncRNAs have potential as novel prognostic markers and therapeutic targets, providing valuable insights for personalized CRC treatment strategies.